Differentiated Learning in IPAS Subject to Enhance Fourth-Grade Critical Thinking - Sukma, Hanum Hanifa (International Journal of Education and Learning, 2025)
This study employs a qualitative research method and was conducted at SD Muhammadiyah Karangkajen Yogyakarta, utilizing data sources that include the IPAS teacher for grade IV. Data collection techniques encompassed observation, interviews, and documentation. The validity of the data was ensured through source and technique triangulation. Data analysis followed the Miled and Huberman model, involving the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that that the implementation of differentiated instruction to support critical thinking in fourth-grade students at SD Muhammadiyah Karangkajen Yogyakarta in the IPAS subject involves differentiated processes. The differentiation process encompasses a series of activities in learning, including thought- provoking questions, material delivery, active and enjoyable learning approaches, completion of Student Worksheets (LKPD), presentations, and evaluations. In this context, various aspects that support students' critical thinking abilities, such as interpretation, analysis, self-regulation, inference, explanation, and evaluation, can be observed in a conducive and enjoyable learning environment for the students.